Use of Trained Non-Medical Staff to Improve Access to HIV Testing Services in Africa: Implementation of the World Health Organization Opt-out Approach in Cameroon - Charles Kouanfack; Skinner Lekelem; Fala Bede; Ngwayu Claude Nkfusai; Yvette Nouafo; Christian Tchokonte; Nicaise Zephirin; Pierre Joseph Fouda (Global Health and Education Projects, Inc., 2021)
Background: The Joint United Nations Programme on HIV/AIDS (UNAIDS) in 2019 estimated that 450,000 to 50,000 people in Cameroon were living with HIV, yet only 79% knew their HIV status which is far from the 90% target for 2020. To address this situation, Cameroon adopted the "Opt-out" strategyof the World Health Organization (WHO) and use of trained non-medical cadre (psychosocial agents) to reach out to more people with HIV testing services (HTS). This describes the implementation and outcomes of this strategy by reviewing the activity of a typical day in the Yaoundé Central Hospital (YCH) in Cameroon. Methods: HTS were offered to hospitalized and ambulatory patients (including their companions) in different departments of the YCH. Following screening for recent HIV testing, those with unknown HIV status that gave consent or did not explicitly refuse testing (as per the "Opt-out Strategy"), were counseled and tested for HIV. Testing followed the "National HIV Rapid Testing Algorithm" using rapid diagnostic test kits. Results were either positive, negative or indeterminate. Patients with positive HIV results were linked to the Care and Treatment Center for treatment initiation. Results: Of the 350 patients screened and offered HTS using non-medical cadre (psychosocial agents), 193 (55.1%) were hospitalized and 157 (44.9%) came for outpatient visits. The age of participants ranged from 14 to 92 years and the yield of HIV testing in the sample population was 5.1% (6.2% for hospitalized patients and 3.8% for outpatient clinics). Statistics revealed that five HIV-positive patients had never been offered HTS before the study. The study revealed that HTS acceptance rate among hospitalized patients was 69.6% and that all new positive patients started antiretroviral treatment on the same day. Conclusion and Global Health Implications: It is feasible to use trained non-medical staff for HIV testing services (HTS). Task-shifting by using trained psychosocial agents can help in case identification and linkage to HIV treatment services.   Copyright © 2021 Kouanfack et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.